FRIT-based integral action state feedback controller tuning using PSO for a liquid slosh suppression system - Nurul Najihah Zulkifli; Mohd Syakirin Ramli; Hamzah Ahmad; Addie Irawan (Bulletin of Electrical Engineering and Informatics, 2022)
This paper presents a model-free approach of controller tuning to a liquid slosh suppression system. The sloshing is the usual occurrence happening to the liquid in a moving container. An integral action state feedback controller was proposed as the selected control structure. A fictitious reference signal was formulated using the recorded input-output data generated from a one-shot experiment and later be used to design the appropriate performance index. The minimization of the performance index of the controlled system was achieved by employing the PSO algorithm. Numerical analyses using MATLAB software have been conducted to evaluate the effectiveness of the proposed model-free approach. The results manifested that the tuned controller had exhibited good transient response performance regarding the trajectory tracking of the cart motion and reduction of slosh level motion.